PROSECUTING SHARIAH OFFENCES IN MALAYSIA: EVIDENTIARY ISSUES - Zulfakar Ramlee Saad (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2019)
The main issue is whether the basic principles of evidence as outlined in Islam and the existing Sharia Court Evidence (Federal Territories) Act 1997 are sufficient to be used in prosecuting Shariah offences in Malaysia. Admittedly Islam, as well as the SCEA 1997, do provide general guidelines on criminal prosecution. However, there are still provisions that need to be improved. The question also arises as to how far forensic evidence can be used in proving these offences. The role of experts will also be studied and also using technology as a part of evidences. This paper will focus on the question of evidential requirements in prosecuting Shariah offences in the Syariah court in Malaysia. Undoubtedly, in realising this intention, it should not only be burdened on the shoulders of the prosecuting officers alone but the role to be played by lawyers, academics and judges will certainly have great impact in solving and improving these shortcomings. Abstrak: Masalah utama dalam penelitian ini adalah apakah prinsip-prinsip dasar bukti yang digariskan dalam Islam dan Sharia Court Evidence (Federal Territories) Act (SCEA) tahun 1997 cukup untuk digunakan dalam penuntutan pelanggaran Syariah di Malaysia. Islam and SCEA 1997 memang memberikan pedoman umum berkaitan dengan penuntutan pidana. Namun, beberapa ketentuan masih perlu diperbaiki. Pertanyaan lain yang juga muncul adalah sejauh mana bukti forensik dapat digunakan dalam membuktikan pelanggaran ini. Peran para ahli juga akan dipelajari dan teknologi akan digunakan sebagai bagian dari bukti. Artikle ini fokus pada pertanyaan persyaratan bukti dalam menuntut pelanggaran syariah di pengadilan syariah di Malaysia. Tidak diragukan lagi bahwa tanggung jawab mewujudkan hal ini seharusnya tidak hanya dibebankanpada para jaksa penuntut saja tetapi dibutuhkan peran pengacara, akademisi dan hakim yang tentu akan berdampak besar dalam menyelesaikan dan memperbaiki kekurangan-kekurangan yang ada. Kata Kunci: Pelanggaran Syariah, Isu Pembuktian, Hukum Pidana Islam